2014
DOI: 10.1111/hepr.12348
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate reductase C677T gene mutation and hyperhomocysteinemia in Budd–Chiari syndrome and portal vein thrombosis: A systematic review and meta‐analysis of observational studies

Abstract: Homozygous MTHFR mutation and hyperhomocysteinemia may be associated with the occurrence of BCS and non-cirrhotic PVT. In addition, homozygous MTHFR mutation may increase the risk of PVT in cirrhotic patients. However, the current evidence failed to support the association of hyperhomocysteinemia with PVT in cirrhotic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 57 publications
2
28
1
1
Order By: Relevance
“…A recent systematic review has demonstrated that a homozygous MTHFR C677T mutation and hyperhomocysteinemia increase the risk for noncirrhotic PVT [39]. Similarly, our study found a very high prevalence of the MTHFR C677T mutation in Chinese patients with PVT (76%).…”
Section: Discussionsupporting
confidence: 84%
“…A recent systematic review has demonstrated that a homozygous MTHFR C677T mutation and hyperhomocysteinemia increase the risk for noncirrhotic PVT [39]. Similarly, our study found a very high prevalence of the MTHFR C677T mutation in Chinese patients with PVT (76%).…”
Section: Discussionsupporting
confidence: 84%
“…Recently, it has been also proposed that the identification of thrombotic risk factors for PVT should be helpful to stratify the benefits of prophylactic anticoagulation in liver cirrhosis [28, 29]. However, we have to acknowledge that few thrombotic risk factors for PVT have been clearly established in a small number of patients with liver cirrhosis [3033]. In addition, anticoagulation could be effective for the treatment of PVT in liver cirrhosis [3437].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperhomocysteinaemia is associated with an increased risk of venous thrombosis in the general population. A systematic review and meta‐analysis demonstrated that BCS patients had a significantly higher prevalence of hyperhomocysteinaemia and homozygous MTHFR C677T mutation than healthy controls . In Europe, prevalence of hyperhomocysteinaemia in BCS patients ranges from 11% to 22% in published studies, whereas it seems to be double the prevalence in China …”
Section: Aetiology and Pathogenesismentioning
confidence: 99%